Jumping versus nonjumping anterior cruciate ligament injuries : A comparison of pathology - Paul, J. J.; Spindler, K. P.; Andrish, J. T.; Parker, R. D.; Secic, M.; Bergfeld, J. A. (Clinical Journal of Sport Medicine, 2003)
Objective: To compare pathology in knees with an anterior cruciate ligament (ACL) injury as a result of a jumping mechanism with knees injured from a nonjumping mechanism. Design: This was a prospective study of 263 consecutive patients with a complete ACL tear and no subsequent giving way episodes nor reinjuries prior to undergoing an ACL reconstruction. The patients were placed into one of two groups: those with knees injured as a result of a jumping injury, and those with knees injured as a result of a nonjumping injury. Setting: This study was performed at the Cleveland Clinic Foundation, Cleveland, Ohio. Patients: Anterior cruciate ligament-deficient knees undergoing ACL reconstruction. Two hundred thirty-eight (91%) of the patients were injured while participating in sports. Main Outcome Measured: Intra-articular pathology documented prospectively at the time of arthroscopy. Results: Knees injured as a result of a jumping mechanism had a higher incidence of medial (p = 0.05) and lateral (p = 0.03) meniscal tears and a lower incidence of medial collateral ligament injuries (p = 0.05). No difference in arthroscopic articular cartilage injuries was seen between the two groups. Conclusions: We believe that identifying jumping as a mechanism of ACL tears is important, since a jumping mechanism is associated with a significantly increased meniscus tear rate and may predispose this population to future degenerative changes.